Invasion of Meningioma Cell in Bony Hyperostosis- an Observational Study of 34 Cases - Satter, AM Rejaus; Talha, KA; Rashid, Farzana; Selina, Farhana; Khan, Md. Mamun; Hossain, ATM Mosharef; Shaikh, Abdul Kader (Bangladesh Journal of Neuroscience, 2014)
Background: Meningiomas are usually globular encapsulated tumors. They are extra axial tumors attached to dura and compress the underlying brain without invading it. Abnormalities of bone are frequently encountered in Meningiomas. Hyperostosis or endosotsis are certainly more common than destruction of bone. Aims and Objective: Aim of study was to observe the percentage of tumour cell invasion in to the hyperostosis part of intracranial meningiomas. Materials and methods: This is an observational analytic study. Sample size was 34. Place of study was department of Neurosurgery of Square Hospitals Ltd. All the patients with the histological diagnosis of meningioma were included in to this study. Result: Female patients were predominant. Highest number of patients was from 41 to 50 years age group. Convexity meningiomas were commonest (35%) followed by parasagittal meningiomas. According to histopathological subtype meningothelimatous was commonest (56%) followed by psammomatous. About one fourth meningioma patients (26.47%) presented with hyperostosis. Among the hyperostosis patients in 44.44% patients cause of hyperostosis was due to tumour cell invasion into hyperostosis part. Conclusion: Tumour cell invasion is one of the causes of hyperostosis in intracranial meningiomas which was responsible in more than one third cases in this study. Bangladesh Journal of Neuroscience 2011; Vol. 27 (2) : 78-82 DOI: http://dx.doi.org/10.3329/bjn.v27i2.17573